Pengaruh Pengetahuan Investasi, Manfaat Investasi, Motivasi Investasi, Modal Minimal Investasi, Dan Return Investasi Terhadap Minat Investasi Di Pasar Modal - Wulandari, Putri; Machmuddah, Zaky; Utomo, ST. Dwiarso (Universitas Dian Nuswantoro, 2023)
This research was carried out to see whether there was an influence on investment knowledge, investment benefits, investment motivation, minimum investment capital and investment returns on investment interest in the capital market. Quantitative methods were used in this research. Determining sample limits using the Slovin formula produced 201 respondents from 405 students who took part in KSPM in Semarang City. The samples for this research were Unissula 15 students, Unisbank 10 students, UIN Walisongo 17 students, Unwahas 5 students, Polines 49 students, Undip 50 students, Unika 10 students, Udinus 28 students, Upgris 10 students, Usm 7 students. This research was conducted using primary data, namely multiple linear regression analysis tests. From the test results, investment knowledge, investment benefits, investment motivation, minimum investment capital and investment returns have an influence on investment interest in the capital market among students who take part in KSPM in Semarang City. The results of the F test show that the significance value is 0.000, which means less than 0.05, indicating that this model can be used for research. Based on the results of the Adjusted R Square test, the value is 0.585 or 58.5%, indicating that the five independent variables have an effect on the dependent variable by 58.5%. Meanwhile, the remaining 41.5% of investment interest among students who take part in KSPM is influenced by other variables that are not in the regression model of this research.